The challenges of teaching in Basic Education during the COVID-19 pandemic in Lábrea – Amazonas - Brazil - Cavalcante dos Santos, Eliana (2022)
The experience of the COVID-19 pandemic brought changes in the teaching and learning process in Basic Education, especially in the transition from the face-to-face format to Emergency Remote Teaching (ERE). Given this situation, this article sought to understand how the teaching practice was produced with the use of digital technologies during the ERE experience in the city of Lábrea, state of Amazonas, Brazil. For this, the research was based on a methodology with a qualitative approach and was built from participant observation, registration in a field diary and application of a semi-structured questionnaire. The data construction process was carried out between February and March 2021, in which 21 Basic Education teachers from that city participated, and Content Analysis was used as a technique for the analysis procedure, mainly in the ordering and systematization of their activities. activities. The research results reflected some challenges that teachers faced during this experience, such as: fear of contagion of the disease and uncertainties about professional training, internet access, lack of diversity of technological tools and effectiveness of the learning process. Finally, the text presents the teaching practice that is forged in everyday life between the expectations of innovations proposed by digital technologies and the multiplicity of social arrangements, such as the precariousness of internet access during the COVID-19 pandemic.